What's Happening? Banality and Intimacy in Mobile and Social Media - Crawford, Kate (Humanities Australia, 2010)
And what, exactly, is it that keeps people, especially young adults, jabbering away into the mobiles held to their ears, or the microphones dangling from their necks? What portentous information, what profound philosophical insight, is it that can't wait until they are home again, or in the actual physical presence of their interlocutor?